Family problems and sports performance - Ritvo, E. C.; Glick, I. D. (The Physician and Sportsmedicine, 2005)
The incidence of psychiatric disorders and family problems in elite athletes is probably similar to that of the general population, yet, for a variety of reasons, athletes and their families rarely seek treatment. Athletic performance may be affected by problems in a marriage or home life, as in this case of a high-profile athlete whose wife abused medications and alcohol to cope with a depressive disorder and anxiety. Clinicians who treat athletes should be aware of family dynamics that may affect performance and be willing to suggest interventions, such as individual and marital psychotherapy, medication, or both.